Regenerative graft materials for maxillary sinus elevation in randomized clinical trials: A meta-analysis - S.A. Alkaabi; G.A. Alsabri; D.S. Natsir Kalla; S.A. Alavi; R. Nurrahma; T. Forouzanfar; M.N. Helder (Elsevier, 2022)
Background: Maxillary sinus floor augmentation (MSFA) is a procedure to restore vertical bone defects in the posterior maxilla. Randomized clinical trials (RCT) are considered a golden standard to investigate the efficacy of treatments. We aimed to conduct a systemic review and meta-analyses of RCTs using regenerative materials for MSFA, and to evaluate the risk of bias (RoB) which can still affect trial validity. Methods: Cochrane Oral Health Group's Trials Register, the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, EMBASE and Google Scholar were searched up to December 2020. After outcome assessments and meta-analyses, the articles underwent quality assessment methods (according to the Jadad scale and the Delphi list) to evaluate the RoB. Results: Thirty-two studies were included. The meta-analyses found no significant difference between regenerative materials and non-regenerative grafts in new bone formation, augmented bone height, soft tissue area, total bone volume and bone density, but displayed a significant difference in terms of residual bone graft. None mentioned quality assessment methods in their trial. Eighteen out of 32 failed to describe the way of randomisation, 23 studies did not declare a double blinded approach, and 30 studies failed to clarify their blinding procedure. Moreover, allocation concealment (28 studies), intention to treat (32 studies), and patient awareness (29 studies) were not described or mentioned properly in the trials. Conclusion: Meta-analysis showed no significant preference in using regenerative over non-regenerative grafts except when using bone substitutes. The high RoB observed in RCTs implies that quality improvement of CTs is necessary.